Application of Importance Performance Analysis Method for Service Identification in the Learning Process - Michael George Sumampouw; Liza Wikarsa; Axl Marselino Rumondor (Journal of Information Technology and Its Utilization, 2024)
The learning process is a series of activities and interactions that occur as individuals acquire new knowledge, skills, attitudes or understanding through various means. Responses and feedback in the context of the classroom, practical experience or other learning resources are integral to this process. The Importance Performance Analysis (IPA) method is used to identify, measure, and evaluate the importance and performance of components in a system or organization. This study proposes a web-based application, namely Application of Importance Performance Analysis Method, to digitize the process of identifying service attributes in learning at the Faculty of Engineering, De La Salle Catholic University Manado. Using the IPA method, this application assists decision makers in formulating effective strategies and policies to improve the quality of education. The method used to develop this application is the Rapid Application Development method. This solution overcomes complicated data processing problems and provides convenience in compiling reports on the learning process every semester.